Improvement of students’ creative writing literacy at SMPN 16 Malang - Daroe Iswatiningsih; Joko Widodo; S. Sutawi; Anis Dwi Winarsih; Prilla Lukis Wediya (Universitas Muhammadiyah Malang, 2023)
The objective of the community service carried out by a team from Universitas Muhammadiyah Malang at SMPN 16 Malang is to increase students’ creative writing literacy. The methods used were training and mentoring during creative writing. The activity began with recording students’ writing interests and identifying the students' type of writing preferences, followed by training, writing practice, evaluating student work, strengthening student understanding, and improving the written work. To achieve the activity’s targets, students were requested to answer questions on a Google form. The result shows that 178 students have an interest in writing, of which 79% chose to write stories, 19% wrote poetry, and the rest chose fables and history. Students who were interested in writing were given training and practice. The training includes strengthened writing concepts, writing practice, result assistance, and feedback. Training activities, mentoring, and enhancement of student work are carried out for three months. Furthermore, the process of editing and designing the book was carried out for one month. At the end of the activity, 78 students could write short stories, descriptive stories, and poetry. After going through the curation and editing process, the students' work was recorded with an International Standard Book Number (ISBN) and given to each author and the school.